Modes of telling the Graphics News in Northern Argenti - Arrueta Parraga, César (2013)
The aim of this paper is to approach and to understand the ways that three newspapers of northern Argentina (Pregón, El Tribuno de Salta and El Liberal) tell the news, considering the first stylistic level and the second net graphical-spatial level. Based on this, it proposes a critical reflection on the mechanisms and modalities applied on the redaction surface, identifying needs and challenges in the context of the demands of the digital world and the transformation of media consumption habits. The main conclusions, there is a predominance textual classic/conservator on innovative visual forms, a graphical prevalence of the advertising guideline and publishing priorities on the news frames, an aesthetic